Case Report: Severe HHV-6-related encephalitis following anti-CD19 CAR-T therapy with no evidence of HHV-6 reactivation in transduced CAR-T cells - Birk, Nina Marie; Kielsen, Katrine; Met, Özcan; Haastrup, Eva Kannik; Hulen, Thomas M.; Madsen, Cecilie Ø.; Barington, Torben; Nielsen, Jonas; Schønning, Kristian; Petersen, Søren Lykke; Ifversen, Marianne (Frontiers in Hematology, 2025)
We report a case of severe encephalitis caused by human herpes virus 6 (HHV-6) following CD19 chimeric antigen receptor T (CAR-T) cell therapy. Rapid expansion of circulating T-lymphocytes and high HHV-6 viral load (4,500,000 DNA copies/mL) early after CAR-T infusion suggested HHV-6 transferal from autologous CAR-T cells. To investigate this hypothesis, we retrospectively analyzed cryo-preserved patient samples for HHV-6. HHV-6 was undetectable in the apheresis product, transduced CAR-T cells, and in vitro activated CAR-T cells. In conclusion, despite strong clinical suspicion, we found no evidence to substantiate the infused CAR-T cells as the source of the severe HHV-6 infection.